In Silico and In Vitro Antibiofilm Activity of Zingiber montanum Ethyl Acetate Fraction Against Propionibacterium acnes: Antibiofilm of Zingiber montanum - Aji, Nur; Kumala, Shirly; Mumpuni, Esti; Rahmat, Deni (Journal of Tropical Life Science, 2025)
Propionibacterium acnes (P. acnes), a symbiotic bacterium involved in the development of acne, is recognized for its capacity to develop resistance due to its ability to generate biofilms. According to a previous investigation, the ethyl acetate fraction derived from Zingiber montanum exhibited anti-bacterial properties against P. acnes. Nevertheless, the causative role of biofilm formation in its resistance was not previously recognized. This study aims to ascertain the antibiofilm efficacy using in silico and in vivo methodologies. In this study, in silico examination utilized molecular docking to inhibit the quorum sensing mechanism by blocking the autoinducer 2 (AI-2) signal. The target protein was AI-2 binding periplasmic protein LuxP (PDB code: 4YRZ). Following that, an in vitro test was conducted using the crystal violet staining method, which was read using a microplate reader at a wavelength of 600 nm. The readings were expressed as percent inhibition and IC50. The in silico results showed that there were six compounds in the ethyl acetate fraction that have the potential to inhibit AI-2 signaling. Curcumin showed the highest inhibitory activity. Meanwhile, the in vitro results revealed that the ethyl acetate fraction of Z. montanum obtained the minimum biofilm inhibitory concentration (MBIC) of 2.5 % (w/v) and IC50 = 0.28 % (w/v). It can be concluded that the ethyl acetate fraction of Zingiber montanum could inhibit the biofilm formation of P. acnes.